2008
DOI: 10.2527/jas.2007-0482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feedlot management system on response to ractopamine-HCl in yearling steers1

Abstract: Two experiments evaluated the effects of conventional and natural feedlot management systems (MS) on ractopamine-HCl (RAC) response in yearling steers. Feedlot performance, carcass characteristics, skeletal muscle gene expression, and circulating IGF-I concentrations were measured. The conventional system included a combined trenbolone acetate and estradiol implant, Revalor-S (IMP), as well as monensin-tylosin feed additives (IA). Treatments were arranged in a 2 x 2 factorial and included: 1) natural (NAT): no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 29 publications
6
31
1
2
Order By: Relevance
“…This agrees with observations of Quinn et al (2008), who observed no difference in ADG between heifers supplemented with RAC for 28 d and control heifers fed 0 mg RAC (P > 0.10). These researchers observed only a tendency for RAC to improve G:F (P = 0.06).…”
Section: Growth Performancesupporting
confidence: 82%
See 1 more Smart Citation
“…This agrees with observations of Quinn et al (2008), who observed no difference in ADG between heifers supplemented with RAC for 28 d and control heifers fed 0 mg RAC (P > 0.10). These researchers observed only a tendency for RAC to improve G:F (P = 0.06).…”
Section: Growth Performancesupporting
confidence: 82%
“…These results coincide with observations of Quinn et al (2008), who reported that supplementation of RAC to heifers did not impact HCW or LM area (P > 0.10). In contrast, and observed improvements in HCW and LM area in steers supplemented with RAC (P > 0.05).…”
Section: Carcass Analysessupporting
confidence: 82%
“…Hence, the high level of supplementation in the present study could have overridden the effect of the β-agonist on insulin concentrations. However, the better BCS of the cattle in this study also may have influenced the lack of effect, as neither zilpaterol nor ractopamin have been shown to affect serum concentrations of insulin in fed steers in good BCS (Winterholler et al, 2008;Carroll et al, 2014). Nevertheless, similar to previous findings (Guzmán et al, 2012), insulin concentrations was not associated with the response to oestrus stimulation, suggesting that relative to IGF-I and leptin, insulin may have less of an effect on the control of reproduction in cattle.…”
Section: Discussionmentioning
confidence: 83%
“…Muscle mass influences BCS only at the lower range of the body condition scale (⩽4) (Apple et al, 1999;BIF, 2010). However, the use of β-AA provoked a change in body composition by increasing muscle accretion (Winterholler et al, 2008;Holland et al, 2010). Moreover, to avoid the direct effect of nutrient intake and/or β-AA treatment on follicular development and gonadotrophin secretion both treatment and feed supplementation were suspended prior to the initiation of the oestrus induction treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation